(untitled) (Research, Society and Development, 2026)
Physics teaching in Brazilian high schools faces challenges related to student engagement and the effective construction of scientific knowledge. In order to understand the scientific production on Physics teaching at the high school level, this study aimed to investigate, through a bibliometric analysis, the methodological approaches adopted in Physics teaching, with an emphasis on active methodologies. The research was based on articles indexed in the Scopus database, selected according to the stages of the PRISMA protocol. To support the screening process, the Rayyan tool was used, while the VOSviewer software was employed for data visualization and analysis. The analyses included collaboration networks among authors and countries, as well as keyword occurrence. In total, 148 publications comprised the analysis corpus. The results indicate that scientific production is still limited, showing growth from 2015 onwards, reflecting a recent interest in the topic. A concentration of academic impact was observed among a small number of authors. Regarding geographic distribution, Indonesia stands out for the highest number of publications, while Turkey showed the greatest scientific impact in terms of citations. Keyword analysis revealed a shift in research focus, moving from discussions centered on engagement to approaches focused on conceptual understanding and the use of educational technologies. Overall, it is concluded that, although still incipient, scientific production is strengthening, highlighting the need to expand studies that support innovative pedagogical practices in Physics teaching.